COVID-19 and the Curse of Piecemeal Perspectives - Walzer, Chris (Frontiers in Veterinary Science, 2020)
The world is in turmoil. A novel coronavirus (SARS-CoV-2) has catapulted across the ever-evolving interface between humans and wild places relentlessly spreading coronavirus disease (COVID-19) amongst humans and bringing immense suffering and death to the farthest reaches of our planet. What was immediately apparent was that the virus responsible for this outbreak originated in wild animals. A wildlife source does not come as a surprise as the majority of emerging infectious diseases are zoonotic and two-thirds have their origin in wildlife. The commercial use of wildlife for consumption encompassing both legal and illegal trade is poorly regulated with porous boundaries between the two entities. This trade, particularly in live animals, creates super-interfaces along the food value chain co-mingling species from many different geographies and habitats while creating perfect conditions for the exchange and recombination of viruses. Since the SARS outbreak in 2002/2003, broad scientific consensus exists that long term, structural changes, and wildlife trade and market closures will be required to prevent future epidemics. The pragmatic, most cost-effective action governments can take with immediate effect is to ban the commercial trade of wild birds and mammals for consumption. Most importantly, this reduces the risk of future zoonotic transmission while also safeguarding resources for those Indigenous Peoples and local communities who rely on wild meat to meet their nutritional requirements.